Multiorgan Dysfunction and Associated Prognosis in Transthyretin Cardiac Amyloidosis - Adam Ioannou; Christian Nitsche; Aldostefano Porcari; Rishi K. Patel; Yousuf Razvi; Muhammad U. Rauf; Ana Martinez‐Naharro; Lucia Venneri; Antonella Accietto; Lucrezia Netti; Francesco Bandera; Ruta Virsinskaite; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Transthyretin cardiac amyloidosis (ATTR‐CA) is a progressive and ultimately fatal cardiomyopathy. Biomarkers reflecting multiorgan dysfunction are of increasing importance in patients with heart failure; however, their significance in ATTR‐CA remains largely unknown. The aims of this study were to characterize the multifaceted nature of ATTR‐CA using blood biomarkers and assess the association between blood biomarkers and prognosis. Methods and Results This is a retrospective cohort study of 2566 consecutive patients diagnosed with ATTR‐CA between 2007 and 2023. Anemia (39%), high urea (52%), hyperbilirubinemia (18%), increased alkaline phosphatase (16%), increased CRP (C‐reactive protein; 27%), and increased troponin (98.2%) were common findings in the overall population, whereas hyponatremia (6%) and hypoalbuminemia (2%) were less common. These abnormalities were most common in patients with p.(V142I) hereditary ATTR‐CA, and became more prevalent as the severity of cardiac disease increased. Multivariable Cox regression analysis demonstrated that anemia (hazard ratio [HR], 1.19 [95% CI, 1.04–1.37]; P=0.01), high urea (HR, 1.23 [95% CI, 1.04–1.45]; P=0.01), hyperbilirubinemia (HR, 1.32 [95% CI, 1.13–1.57; P=0.001), increased alkaline phosphatase (HR, 1.20 [95% CI, 1.01–1.42; P=0.04), hyponatremia (HR, 1.65 [95% CI, 1.28–2.11]; P<0.001), and troponin‐T >56 ng/L (HR, 1.72 [95% CI, 1.46–2.03]; P<0.001) were all independently associated with mortality in the overall population. The association between biomarkers and mortality varied across the spectrum of genotypes and left ventricular ejection fraction, with anemia remining independently associated with mortality in p.(V142I) hereditary ATTR‐CA (HR, 1.58 [95% CI, 1.17–2.12]; P=0.003) and in a subgroup of the overall population with a left ventricular ejection fraction ≤40% (HR, 1.39 [95% CI, 1.08–1.81]; P=0.01). Conclusions Cardiac and noncardiac biomarker abnormalities were common and reflect the complex and multifaceted nature of ATTR‐CA, with a wide range of biomarkers remaining independently associated with mortality. Clinical trials are needed to investigate whether biomarker abnormalities represent modifiable risk factors that if specifically targeted could improve outcomes.